Analyzing the Impact of Bank Syariah Indonesia Merger on Financial Efficiency Using DEA and Tobit Models - Wahyuni, Iis; Afiq, Muhammad Raihan (Institut Bisnis dan Informatika Kesatuan, 2024)
Sharia Bank is one of the sharia financial services industries that has a role in economic development in Indonesia along with the real sector because banking is an intermediary institution. However, the impact of the Covid-19 pandemic, sharia banks face major problems to survive due to changes in consumption patterns, lifestyle patterns, and regulations. In an effort to encourage the development of sharia banks in Indonesia, the government has issued various regulations such as the implementation of sub-policies and new policies, namely the merger of 3 state-owned sharia banks. The three sharia banks are Bank BRI Syariah, Bank BNI Syariah and Bank Mandiri Syariah. The establishment of Bank Syariah Indonesia (BSI) is a government strategy to make Indonesia one of the world's sharia financial centers. The purpose of this study is to determine whether mergers can affect the efficiency of a bank by using the variables of asset structure, return on assets, return on equity, capital adequacy ratio, and non-performing financing. This research uses a quantitative method using a quantitative descriptive method. The type of data used in this study is secondary data obtained through the official website of the Indonesia Stock Exchange (IDX) available at www.idx.co.id in the form of monthly financial reports from Bank Syariah Indonesia. The population in this study is Bank Syariah Indonesia (BSI) listed on the Indonesia Stock Exchange (IDX) in 2021 - 2024. In this study, the sampling technique used is purposive sampling. The object of this study is the selection of input and output variables to calculate the level of efficiency using the Data Envelopment Analysis (DEA) method at the First Stage and using the Tobit Model at the second stage. The data analysis method uses descriptive statistical analysis and hypothesis testing using the Wilcoxon Signed Rank Test. The results of this research are that mergers carried out in banking can lead to increased efficiency and stability. This study also concludes that the variables of assets, return on assets, return on equity, capital adequacy ratio, non-performing financing have a positive and significant effect on bank efficiency. Keywords: Merger, Sharia Banks, Efficiency, Data Envelopment Analysis, Tobit Method.